Complexes built the women of the ottoman court in the 19th century, an evaluation of their contribution to istanbul's urban texture - ŞAHİN, PINAR (My University, 2022)
The 19th century was the century in which the urban fabric of Istanbul underwent its biggest transformation. During this period when the reform movement gained momentum, the state carried out a Western-style restructuring and introduced many new city planning regulations. Among the important developments that took place in this period after municipalities were established in 1855 were significant changes to the city plan and the building regulations put in place to facilitate and coordinate the residential areas and constructions. This process affected all spheres of society and the women of the Ottoman court emerged as commanding figures. These women left their mark on Istanbul\"s urban fabric thanks to the constructions and repair of social, military, and secular architecture which they brought about either using personal savings or state funding. Modem city planning gave Ottoman construction projects a new direction, it is evident that the numbers of buildings named after and funded by the women of the Ottoman court in the 19th century gathered momentum, and these structures have left their mark on Istanbul\"s skyline. This article deals with the edifices built by ladies of the Ottoman court, namely the Sah Sultan Complex (1800), the Naksidil Valide Sultan Complex (1818), the Bezmialem Gureba Muslimin Hospital Complex (1845), the Bala Suleyman Aga Complex (1863) and the Aksaray Valide Sultan Complex (1871). These buildings have been studiedtheir location and structural features and they were examined on contemporary maps.

19. yüzyıl İstanbul’un kent dokusu açısından en büyük değişim yaşadığı asırdır. Reform hareketlerinin yoğunluk kazandığı bu dönemde devletin merkez teşkilatının batılı tarzda yeniden düzenlenmesi yanında şehircilik faaliyetleri açısından da birçok yeni uygulama yapılmıştır. 1855’ten sonra belediyelerin kurulması ile birlikte şehir planında önemli değişikliklerin yapılması, yerleşim alanlarının ve inşa faaliyetlerinin düzenlenmesi için ebniye nizannamelerinin hazırlanması bu dönemde meydana gelen önemli gelişmelerdir. Toplumsal hayatın her alanını etkileyen bu süreçte, Osmanlı saray kadınları baskın bir figür olarak karşımıza çıkmaktadır. Gerek şahsi birikimleri gerekse de devlet desteği ile inşa ve tamir ettirdikleri sosyal, askeri ve sivil yapılarla İstanbul şehir dokusunda kalıcı izler bırakmışlardır. Modern şehircilik kavramının Osmanlı bayındırlık faaliyetlerine yeni bir yön verdiği 19. yüzyılda saray kadınlarının İstanbul’un silüetine damgasını vuran eserlere giderek artan bir ivme ile isimlerini verdikleri görülmektedir. Bu makalede saray kadınlarının inşa ettirdikleri Şah Sultan Külliyesi (1800), Nakşidil Vâlide Sultan Külliyesi (1818), Bezmiâlem Gurebâ-yı Müslimîn Hastanesi Külliyesi (1845), Bâlâ Süleyman Ağa Külliyesi (1863) ve Aksaray Vâlide Sultan Külliyesi (1871) ele alınmıştır. Araştırmada söz konusu yapılar konumları ve yapısal özellikleri ile dönem haritaları üzerinde incelenmiştir.
19. Yüzyılda Osmanlı saray kadınlarının inşa ettirdiği külliyelerin İstanbul kent dokusuna katkılarının değerlendirilmesi
Keywords: Sosyal ve Beşeri Bilimler; Sanat; Social Sciences and Humanities; Art; SANAT; Sanat ve Beşeri Bilimler; Sanat ve Beşeri Bilimler (AHCI); ART; ARTS & HUMANITIES; Arts & Humanities (AHCI); General Arts and Humanities; Arts and Humanities (miscellaneous); Conservation; Museology; Visual Arts and Performing Arts; Social Sciences & Humanities; Ottoman Court women; Istanbul's urban fabric; the Westernisation period; Complexes; Modern town planning; Osmanlı saray kadınları; İstanbul kent dokusu; Batılılaşma dönemi; Külliyeler; Modern şehircilik; Ottoman Court women; Istanbul’s urban fabric; the Westernisation period; Complexes; Modern town planning